Protection of companion animals upon the death of their owner in Peruvian law - Marín M., Alessandra (2024)
Companion animals lack succession rights because in Peruvian law there is no absolute freedom to testate, so it is necessary to find the legal figure that allows their owners to have the possibility of arranging their protection when they have died. The present study aims to determine how companion animals could be protected upon the death of the owner in Peruvian law. It is found that, although there is no specific regulation, the figure of the position incorporated in a legacy within the will or in a donation could protect them.